2007
DOI: 10.1377/hlthaff.26.2.w217
|View full text |Cite
|
Sign up to set email alerts
|

Self-Pay Markets In Health Care: Consumer Nirvana Or Caveat Emptor?

Abstract: As consumers face more incentives to make cost-conscious medical care decisions, some policymakers cite self-pay markets as models for consumer shopping. An analysis of the LASIK market revealed limited shopping overall, despite the fact that patients pay the full cost. For other self-pay procedures, consumers shop even less, for reasons ranging from urgency, to costs of obtaining price quotes, to quality concerns that prompt many consumers to rely on word-of-mouth recommendations. Given that consumer shopping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 1 publication
0
18
0
2
Order By: Relevance
“…Now that the gap between the assumptions of demand-driven health care and reality is recognized, measures are being proposed to deal with it. Some suggest that the answer is to educate patients as to how to shop for health care and use performance data [59]. However, our multivariate analysis found that education alone does not mold patients into rational consumers.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Now that the gap between the assumptions of demand-driven health care and reality is recognized, measures are being proposed to deal with it. Some suggest that the answer is to educate patients as to how to shop for health care and use performance data [59]. However, our multivariate analysis found that education alone does not mold patients into rational consumers.…”
Section: Resultsmentioning
confidence: 62%
“…Right from the beginning of hospital certification in the U.S., JCAHO (The Joint commission on Accreditation of Healthcare Organizations) charged a fee for it [62]. This has continued to be a barrier for patients seeking quality information; fees have even increased over time [59]. Two important organizations that rate hospital performance in the U.S., NCQA (National Committee for Quality Assurance) and Healthgrades make minimal information available to consumers for free and charge several thousand dollars for detailed report cards.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Пациенты восприни-мают метод лазерной коррекции зрения как товар и выбирают клинику, руководствуясь только стои-мостью, хотя качество операции сильно отличается в различных клиниках [144] 52 . Кроме того, уверен-ность в себе заставляет людей переоценивать свои знания.…”
Section: получение информацииunclassified